Improving Results Learning Math Student Class I MIS Masheba Through Model Games Two Color Tp 2020/2021 - Yenni Sarmida Nasution; Ari Aprilia Dwiana (STKIP Rokania Pasir Pangaraian, 2021)
, research is aimed to find out whether the model of game two colors can improve the outcomes of learning materials learning addition and subtraction of numbers rounded student clas I MIS Masheba . In this study , the formulation of the problem is how to apply the Two Color Game model in improving results learning materials learning addition and subtraction of numbers rounded student class I MIS Masheba Research is a research action class. Subjects in the study of this is student class I MIS Masheba and its object is the result of learning mathematics student class I MIS Masheba half odd years of teaching of 2020/2021 and the application of models of game two colors. Data collection techniques in this study are tests , observations, and documentation. Based on the analysis it can be concluded that the application of the model of game two colors can improve the results of study of students at the material operations count with competence base about doing addition and subtraction of numbers up to 20 in the student class I MIS Masheba I marked with 89.28% of students in upper grades KKM